The Working Class from Marx to Our Times - Mattos, Marcelo Badaró. author. aut Link
XX, 188 p. 1 illus.
Keywords: “With verve and impressive erudition Marcelo Badaró Mattos tackles a big subject: the historical and sociological debates on Marx’s notion of the working class. Applying a global historical approach, he proves that the concept is—despite the many controversies it has caused—still indispensable for understanding our world. I highly recommend this sophisticated and challenging study.” — Marcel van der Linden, Senior Researcher, International Institute of Social History, The Netherlands ”The Working Class from Marx to Our Times is truly a tour de force, an analytic sweep through the conceptual and practical issues that engage those confronting capitalism and its devastating impact on 21st-century lives. It addresses old thought and new subjects, doing so with exhilarating imagination. A must-read for all who value rigorous intelligence and demand social justice.” —Bryan D. Palmer, Fellow of the Royal Society of Canada “This new book by Marcelo Badaró Mattos takes up a crucial theme of our time: who is the working class and how it is configured. The author takes a suggestive journey to demonstrate how the Marxian conception of the working class is broad and complex and rejects any reductionism.” — Ricardo Antunes, Professor of Sociology, Universidade Estadual de Campinas, Brazil This book reviews Marx’s contributions to the debate on the working class. It also presents exercises of dialogue between Marx’s and Marxists’ discussions on the working class and empirical elements of class reality today, as well as debates in the social sciences and historiography on the same issues. The thesis defended in the book is simple: the “working class,” also called the “proletariat,” as it appears in the work of Karl Marx, had and has validity as an analytical category. Nevertheless, Marx’s discussion on the issue is complex and the category in his approach is wider than many Marxists have presented it. Marcelo Badaró Mattos is Full Professor of Brazilian History at Universidade Federal Fluminense, Brazil. He is the author of Laborers and Enslaved Workers (2017).